FIRST REPORT OF POWDERY MILDEW CAUSED BY ERYSIPHE SP. ON THE CRAPEMYRTLE (Lagerstroemia indica L.) FROM WEST TRIPURA, INDIA - DURGA PRASAD AWASTHI; SUMEN KAPALI; KUNAL DEBBARMA; AMAR BAHADUR (The Bioscan, 2021)
Crapemyrtle (Lagerstroemia indica L.) tree planted for its beauty and elegance were found to be infected with typical symptoms of powdery mildew fungi namely, Erysiphe sp. showing white to creamy white powdery sticky substances on leaves. The fungus was identified based on the morphological characters of the asexual stage like oidial, hyaline and erect hyaline conidiophores having single celled conidia which are cylindrical or ellipsoid in shape and measure about 28–37 × 13.1–15.4μm. Pathogenicity tests were conducted successfully, showing on an average 84.0 % disease incidence on treated plant samples. About 41.11% of average disease severity was recorded among plants grown in field condition. The finding concludes first report of powdery mildew fungi namely, Erysiphe sp. from West Tripura, District of India.